AMH Is a Good Predictor of Metabolic Risk in Women with PCOS: A Cross-Sectional Study. (12th August 2021) - Ou, Miaoxian; Xu, Pei; Lin, Han; Ma, Kaichi; Liu, Mingxing
Abstract : Objective . The relationship between metabolic risk and ovarian function is ambiguous. This retrospective study analyzed the medical records of 461 PCOS patients collected between January 2019 and June 2020 to investigate the relationship between serum anti-Müllerian hormone (AMH) and parameters of metabolic risk in the population with polycystic ovary syndrome (PCOS). Methods . A total of 461 PCOS patients aged 20–40 years were included and stratified into four groups according to the AMH level. The association between AMH and the parameters related to metabolic risk in these groups was compared, and the discrepancies were further explored. Binary logistic regression was performed to examine the risk factors of HOMA-IR. The values of AMH that best predicted the risk of HOMA-IR were also analyzed by ROC curves. Results . AMH was negatively associated with HOMA-IR (odds ratio (OR) −0.279, 95% confidence interval (CI) −0.36 to −0.20), fasting insulin (OR −0.282, 95% CI −0.36 to −0.20), 1-hour postprandial insulin (OR −0.184, 95% CI −0.28 to −0.11), 2-hour postprandial insulin (−0.180, 95%CI −0.28 to −0.11), 3-hour postprandial insulin (OR −0.198, 95% CI –0.30 to −0.13), waist-hip ratio (OR −0.235, 95% CI −0.31 to −0.14), and body mass index (OR −0.350, 95% CI −0.43 to −0.27). There was no statistically significant relationship between blood pressure, serum glucose profile, or lipid levels and AMH. Binary logistic regression showed that AMH protected against the occurrence of PCOS patients (OR: 0.835, 0.776, and 0.898). For the prediction of HOMA-IR, AMH had an AUC-ROC of 0.704 (95% CI 0.652–0.755) with a cutoff value of 7.81 mmol/L, a sensitivity of 70.3%, and a specificity of 70.1%. Conclusions . Higher AMH levels were significantly associated with a lower insulin profile and might be a useful predictor for HOMA-IR in PCOS patients.